Integrasi Nilai Kearifan Lokal dalam Konsep Kecepatan dan Debit pada Pembelajaran Matematika SD - Nurhudayah Manjani; Mardiyah Kharismayanda; May Kurnia Jelita; Sri Halimah; Mutiah Sinaga; Eka Rismaynarti Br Purba (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2025)
The skill to comprehend and implement speed and discharge concepts is vital in mathematics education, yet students often face hurdles in this area. These difficulties can stem from inadequate basic knowledge, limited hands-on experience, or a lack of teacher support. This research centers on the challenges 5th-grade elementary students encounter in mastering speed and discharge. Utilizing a qualitative methodology, the study relies on secondary data derived from literature reviews, specifically an SLR (Systematic Literature Review). The study's outcomes reveal that students struggle with core concepts, basic math operations, word problem comprehension, and real-world application. To alleviate these difficulties, a more contextual teaching method, sufficient practice, the use of educational technology, and targeted extra guidance are necessary. With effective strategies, students' understanding and proficiency in this subject are expected to improve.